Effectiveness of a Combination of Hypnobreastfeeding and Administration of Lavender Aromatherapy on Reducing Anxiety Regarding Breast Milk Production - Widya Handayani, Ni Nengah; Ari Febriyanti, Ni Made; Ayu Sugiartini, Ni Ketut; Deni Witari, Ni Nyoman (Universitas Islam Jember, 2023)
In the postpartum period, women experience changes in physiological, psychological and social adaptation. One of the psychological disorders that often occurs after giving birth is anxiety when giving breast milk. Anxiety is a feeling of fear that arises for unknown reasons and is not supported by the situation. One effort to reduce maternal anxiety is by providing a combination of hypnobreastfeeding and lavender aromatherapy. The point of this investigate is to decide the viability of hypnobreastfeeding and giving lavender aromatherapy to reduce postpartum mothers' anxiety regarding breast milk production. This investigate plan was a quasi-experiment with a one gather pretest-posttest without control inquire about plan, carried out at Puri Raharja RSU with a test estimate of 42 respondents who met the consideration criteria. The inspecting procedure for this investigate is coincidental testing. Information was collected utilizing the Hamilton Uneasiness Rating Scale (HARS) survey, and information investigation was carried out in stages counting univariate and bivariate (Wilcoxon). The results of bivariate analysis using the Wilcoxon test showed a Z value of -5.675a with a significance level (p=0.000<α 0.05), which means that giving a combination of hypnobreastfeeding and lavender aromatherapy is effective in reducing postpartum mothers' anxiety regarding breast milk production. Midwives can provide counseling on how to reduce anxiety, one of which is by hypnobreastfeeding and giving lavender aromatherapy.